EXAMINING SOCIAL PHYSICS ANXIETY AND EMOTIONAL INTELLIGENCE LEVELS OF THE FACULTY OF SPORT SCIENCES STUDENTS - SARIKABAK, Murat (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2018)
The aim of this study was to examine the social physics anxiety and emotional intelligence levels of the Sakarya University Physical Education and Sports Faculty students. 214 university students voluntarily participated in the study. To collect data in addition to personal information form Turkish versions of “Schutte Emotional Intelligence Scale” and the “Social Physical Anxiety Inventory” were used. SPSS 21 package program was used for statistical analysis and Pearson correlation and independent samples t-test were used to determine the significant correlations and differences. According to analyzed results, in the comparison of age related social physics anxiety levels of the students, a significant difference was found in favor of the students who were above 21 and over in negative evaluation expectation subscale and in social physics anxiety total scores (p <0.05). In the comparison of emotional intelligence scores, a significant difference was found in favor of women according to gender in total scores of optimism / mood regulation sub-dimension and emotional intelligence (p <0.05). Also, a significant negative correlation was found between emotional intelligence and social physical anxiety scores of the participants. As a result, it can be said that the increasing age is a factor in decreasing the anxiety level of the university students, the emotional intelligence levels of women are higher than the men and the social intelligence anxiety decreases as the level of emotional intelligence increases in university students.